A consolidation model for estimating the settlement of warm permafrost. (June 2016) - Zhang, Hu; Zhang, Jianming; Zhang, Zhilong; Chen, Ji; You, Yanhui
Abstract: On the basis of the Biot's consolidation theory, a thermo-hydro-mechanical (THM) model was presented for computing the settlement of warm frozen soils under an external load. The proposed model allowed the unfrozen water in the soils to migrate according to the effective stress principle. In addition, the pressure potential due to loading was considered as the only driving force for the migration of the unfrozen water. The model is validated against an in situ long-term plate loading test that was conducted in a warm permafrost region on the Qinghai–Tibetan Plateau. The computed ground temperature and settlement were consistent with the measured data. Using the model, we analyze the variations of the pore-water pressures at different depths and discuss the influences of the seepage on the deformation, ground temperature and effective stress.